2017
DOI: 10.1177/2047487317724575
|View full text |Cite
|
Sign up to set email alerts
|

Interval training early after heart failure decompensation is safe and improves exercise tolerance and quality of life in selected patients

Abstract: Aims To evaluate safety and efficacy of moderate intensity interval exercise training early after heart failure decompensation on exercise tolerance and health-related quality of life (HRQoL). Methods and results This is a prospective randomized controlled study. We screened 234 consecutive patients admitted with decompensated heart failure; 46 patients (42 men/4 women; 61 ± 12 years of age) were randomized to a moderate intensity aerobic interval training ( n = 24) or to a control group ( n = 22). Patients un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…7 Following proof-of-concept studies by Coats et al 8 and Hambrecht et al 9 which documented the efficacy and safety, respectively, of exercised-based cardiac rehabilitation (ebCR), multiple studies documented its potential to improve functional capacity, QoL and prognosis in patients with heart failure. [10][11][12][13][14][15][16][17] In these studies, however, the populations under investigation were heterogeneous with respect to LV-EF (<35% up to >50%), New York Heart Association (NYHA) classification, and follow-up period. However, the effect of ebCR on morbidity and mortality on top of evidence-based state-of-the-art pharmaco-and device-therapy in high-risk patients with moderately to severely reduced LV-EF is not yet fully established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Following proof-of-concept studies by Coats et al 8 and Hambrecht et al 9 which documented the efficacy and safety, respectively, of exercised-based cardiac rehabilitation (ebCR), multiple studies documented its potential to improve functional capacity, QoL and prognosis in patients with heart failure. [10][11][12][13][14][15][16][17] In these studies, however, the populations under investigation were heterogeneous with respect to LV-EF (<35% up to >50%), New York Heart Association (NYHA) classification, and follow-up period. However, the effect of ebCR on morbidity and mortality on top of evidence-based state-of-the-art pharmaco-and device-therapy in high-risk patients with moderately to severely reduced LV-EF is not yet fully established.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of ebCR on morbidity and mortality on top of evidence-based state-of-the-art pharmaco-and device-therapy in high-risk patients with moderately to severely reduced LV-EF is not yet fully established. [10][11][12][13][14][15][16][17] Although current guidelines recommend ebCR as an effective and safe therapeutic intervention, 1,2,6 HFrEF patients are still clearly underrepresented in CR settings worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Exercise intolerance, frequently manifested by fatigue or shortness of breath on minimal exertion, is a hallmark of HF 1 : one of the principal goals of treatment is to improve exercise capacity, and interventions designed to change this leading symptom in HF have been shown to improve outcomes . ETP is an important adjunct to non‐pharmacological treatment that has a proven positive effects on mortality, morbidity, exercise capacity and quality of life . Based on the analysis of 801 patients enrolled in nine randomized controlled clinical trials, the ExTraMATCH collaborative group calculated a 35% ( P < 0.05) lower risk for mortality and a 28% ( P < 0.05) lower risk for the composite endpoint of mortality or hospitalization in favour of ETP .…”
Section: Discussionmentioning
confidence: 99%
“…Post‐hoc sub‐analyses demonstrated that ETP was effective also in special HF populations . Selection of HF patients for ETP is founded on clinical stability and optimal medical therapy, and its continuation is related to maintaining clinical and therapy stability, treatment adherence, exercise capacity responsiveness and control of psychological factors .…”
Section: Discussionmentioning
confidence: 99%
“…Similar results from a randomised controlled clinical trial in Moscow are published elsewhere in the European Journal of Preventive Cardiology. Doletsky and colleagues 5 found an increase in VO 2peak from 13.6 ml/kg per minute to 15.9 after a 3-week exercise training programme mostly in male heart failure patients (mean age 61 years, New York Heart Association (NYHA) class II-III), and a further increase to 17.4 at 3 months' follow-up, whereas there was no change in the control group. The improvements were paralleled by better MLHFQ quality of life, reduced left ventricular volume, and higher ejection fraction.…”
mentioning
confidence: 98%